Effect of progressive normobaric hypoxia on dynamic cerebral autoregulation. Issue 10 (11th September 2016) - Horiuchi, Masahiro; Endo, Junko; Dobashi, Shohei; Kiuchi, Masataka; Koyama, Katsuhiro; Subudhi, Andrew W.
Abstract : New Findings: What is the central question of this study? Acute hypoxia reduces dynamic cerebral autoregulation (dCA); however, it is unclear what level of hypoxia is necessary to exert this effect. We sought to investigate whether dCA would be reduced during progressive periods of normobaric hypoxia using a duplex Doppler ultrasound technique to evaluate the volumetric blood flow. What is the main finding and its importance? We showed that dCA decreased linearly as inspired O2 decreased from 21 to 12%. Additionally, symptoms of acute mountain sickness were related to changes in dCA. Our results may provide a sensitive and clinically relevant test to evaluate the risk of acute mountain sickness. Cerebral blood flow is maintained at relatively constant levels over a wide range of perfusion pressures via cerebral autoregulation (CA). Although acute hypoxia reduces dynamic CA, it is unclear what level of hypoxia is necessary to exert this effect. We evaluated dynamic CA during progressive normobaric hypoxia (∼1 h at each of 21, 18, 15 and 12% O2 ) using duplex ultrasonography to measure volumetric changes in common carotid artery blood flow of 11 healthy young men. Dynamic CA was evaluated by the thigh‐cuff method and represented as the rate of regulation of vascular conductance. On a separate occasion, symptoms of acute mountain sickness were evaluated during 6 h of prolonged hypoxia (fractional inspired O2 of 14.1%) using the Lake Louise Questionnaire. Repeated‐measures ANOVA with linear trend analysis indicated that dynamic CA decreased progressively as fractional inspired O2 was reduced ( P < 0.001). Spearman rank order analysis revealed that symptoms of acute mountain sickness were related to changes in the rate of regulation of vascular conductance from 21 to 15% ( r = −0.869, P = 0.006) and from 21 to 12% O2 ( r = −0.648, P = 0.040), respectively. These results suggest that dynamic CA worsens with progressive hypoxia and that reductions in dynamic CA during moderate to severe hypoxia (<15% O2 ) may be related to the severity of acute mountain sickness. Abstract :